A dephasing sweet spot with enhanced dipolar coupling - Ungerer, Jann H.; Pally, Alessia; Bosco, Stefano; Kononov, Artem; Sarmah, Deepankar; Lehmann, Sebastian; Thelander, Claes; Maisi, Ville F.; Scarlino, Pasquale; Loss, Daniel; Baumgartner, Andreas; Schönenberger, Christian (Communications Physics, 2025)
Two-level systems (TLSs) are the basic units of quantum computers but face a trade-off between operation speed and coherence due to shared coupling paths. Here, we investigate a TLS given by a singlet-triplet (ST+) transition. We identify a magnetic-field configuration that maximizes dipole coupling while minimizing total dephasing, forming a compromise-free sweet spot that mitigates this fundamental trade-off. The TLS is implemented in a crystal-phase-defined double-quantum dot in an InAs nanowire. Using a superconducting resonator, we measure the spin-orbit interaction (SOI) gap, the spin-photon coupling strength, and the total TLS dephasing rate as a function of the in-plane magnetic-field orientation. Our theoretical description postulates phonons as the dominant noise source. The compromise-free sweet spot originates from the SOI, suggesting that it is not restricted to this material platform but might find applications in any material with SOI. These findings pave the way for enhanced nanomaterial engineering for next-generation qubit technologies.